Preparation method of copper-based catalyst and application of copper-based catalyst in preparation of multi-carbon product by electro-catalysis of CO2

Make copper catalysts by sputtering method and control its layer thickness and current density, combined with replacement reactions to form dual metal catalysts, solve the problem of low selectivity and low activity of the existing copper -based catalysts, and realize the multi -carbon catalytic multi -carbon -made multi -carbon -made multi -carbon -made multi -carbon -based carbon -made multi -carbon -made multi -carbon production The efficient transformation and simplification process of products.

CN119372692APending Publication Date: 2025-01-28ZHEJIANG TIANDI ENVIRONMENTAL PROTECTION TECH CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411482068.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-23
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

When the existing copper-based catalysts are electrocatalytically converted into C2+ products, they have low selectivity and low activity, and the catalyst preparation method is complex, with low yield, making it difficult to prepare on a large scale.

Method used

Copper catalysts are prepared by sputtering method, controlled the thickness and current density of copper spatial layer, and further replace the reaction to form a copper -containing dual -metal catalyst.

Benefits of technology

The efficient conversion of CO2 electrocatalyst multi -carbon products, the carbon product Faraday efficiency (FEC2+) is as high as 65%, simplified the catalyst preparation process, and improved yield and preparation efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119372692A_ABST
    Figure CN119372692A_ABST
Patent Text Reader

Abstract

The invention relates to the field of electrocatalysis, and provides a preparation method of a copper-based catalyst and application of the copper-based catalyst to preparation of a multi-carbon product through electrocatalysis of CO2, the preparation method of the copper-based catalyst comprises the following steps: sputtering copper on a base material, and forming a copper layer with the thickness of 100-500 nm on the surface of the base material to obtain the copper-based catalyst; the particle size of the copper is less than 100 nm; the sputtering power ranges from 100 W to 300 W, and the speed ranges from 10 nm / min to 20 nm / min; or further putting the copper-based catalyst into a metal salt solution for replacement reaction to obtain a copper-containing bimetallic catalyst; and the mass ratio of copper in the bimetallic is 20-50%. The copper-based catalyst is prepared through a sputtering method, and the preparation method is simple and efficient; and proper copper sputtering layer thickness and current density are screened, and FEC < 2 + > reaches up to 65% or above when CO2 is electrically catalyzed to prepare a multi-carbon product.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of electrocatalysis, and in particular to a method for preparing a copper-based catalyst and an application of the copper-based catalyst in electrocatalyzing CO2 to prepare multi-carbon products. Background Art

[0002] The CO2 electrocatalytic reaction is the process of converting electrical energy into chemical energy, storing the excess electrical energy in a series of chemicals that can be used as raw materials or fuels in chemical production processes. The CO2 electrochemical reduction involves a multi-electron transfer process. Depending on the choice of catalyst, the reaction will follow different pathways to produce a series of single carbon (C1) and multi-carbon (C 2+ ) products. Among them, CO2 is electrocatalyzed to C 2+ The products hold great promise, particularly in the production of ethylene and ethanol, both important chemical products.

[0003] Development of efficient electrocatalyst materials for efficient conversion of CO2 to C 2+ The copper-based catalyst is currently the only one that can convert CO2 into C 2+ The metal material of the product, but the low selectivity and low activity of the target product are the main problems of using copper as a catalyst. A series of catalyst preparation methods such as electrodeposition, hydrothermal synthesis and solution replacement methods have been proposed to improve the electrocatalytic reaction performance of CO2. For example, patent CN108677179A discloses the modification of copper foil electrodes and their electrocatalytic reduction of CO2 reaction. The efficiency and selectivity of hydrothermally modified copper foil electrocatalyzing carbon dioxide to produce ethylene are improved. However, these methods usually have problems such as complex catalyst synthesis steps, low yield and difficulty in large-scale preparation. Therefore, an ideal solution is needed. Summary of the invention

[0004] The present invention provides a method for preparing a copper-based catalyst and an application thereof in electrocatalyzing CO2 to prepare multi-carbon products. The copper-based catalyst is prepared by a sputtering method, and the preparation method is simple and efficient. The appropriate copper sputtering layer thickness and current density are selected, and the FEC is obtained when electrocatalyzing CO2 to prepare multi-carbon products. 2+ As high as over 65%.

[0005] In order to achieve the above object, the present invention adopts the following technical solutions: The method for preparing a copper-based catalyst comprises the following steps: Sputtering copper onto a substrate to form a copper layer with a thickness of 100-500 nm on the surface of the substrate to obtain a copper-based catalyst; the particle size of the copper is less than 100 nm; the sputtering power is 100-300 W and the rate is 10-20 nm / min; Alternatively, the copper-based catalyst is further placed in a metal salt solution for a replacement reaction to obtain a copper-containing bimetallic catalyst; the mass proportion of copper in the bimetallic catalyst is 20-50%.

[0006] Preferably, the substrate is carbon paper or PTFE.

[0007] Preferably, the sputtering time is 300-2000 s.

[0008] Preferably, the copper particle size is 50-100 nm.

[0009] Preferably, the copper layer has a thickness of 100-300 nm.

[0010] Preferably, the bimetallic compound is copper and palladium, and the palladium ion concentration in the metal salt solution is 0.3-0.7 mmol / L.

[0011] Preferably, the metal salt solution is a palladium chloride solution, which is prepared from PdCl2 powder, deionized water and hydrochloric acid.

[0012] Preferably, the replacement reaction is carried out at room temperature, and the reaction time is 3-20 min.

[0013] The present invention also provides the use of the copper-based catalyst obtained by the preparation method in electrocatalytic CO2 production of multi-carbon products; the current density is 200-300 mA cm -2 , FEC 2+ >65%.

[0014] Preferably, the current density is 200 mA cm -2 , the thickness of the copper layer is 100-300 nm, FEC 2+ >70%.

[0015] Therefore, the beneficial effects of the present invention are as follows: the copper-based catalyst is prepared by sputtering, and the preparation method is simple and efficient; the appropriate copper sputtering layer thickness and current density are selected, and the FEC is obtained when electrocatalyzing CO2 to produce multi-carbon products. 2+ As high as over 65%. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 The XRD characterization diagrams of copper electrodes with different copper sputtering thicknesses are shown in Figure 1. (a) is a carbon paper-based copper electrode Cu / CP, and (b) is a PTFE-based copper electrode PTFE / CP.

[0017] Figure 2 The SEM electron micrographs of copper electrodes with different copper sputtering thicknesses are shown in Figure 1. (a) is a blank carbon paper, and (b) to (f) correspond to the copper electrodes with a carbon paper loading thickness of 100 to 500 nm in Examples 1 to 5, respectively.

[0018] Figure 3 This is a comparison of the product selectivity of the Cu electrode and the Cu-Pd bimetallic electrode at different current densities. (a) is the Cu electrode, and (b) is the Cu-Pd bimetallic electrode.

[0019] Figure 4 1 is a product distribution diagram of the electrocatalytic reduction of CO2 by Cu / CP. (a) to (e) are product distribution diagrams of the electrocatalytic reduction of CO2 by Cu / CP, corresponding to the copper electrodes C-Cu of Examples 1 to 5, respectively. 100 ~ C-Cu 500 ; (f) is the maximum C of Cu sputtering thickness on electrocatalytic reduction of CO2 2+ The influence of product Faradaic efficiency.

[0020] Figure 5 The catalytic performance comparison of carbon paper-based copper electrode Cu / CP at different current densities is shown in Figure 3. 2+ Faraday efficiency of the product, (b) different thicknesses of carbon paper as substrate C 2+ Effect of fractional current density on the products; Effect of current density on (c) Faradaic efficiency of C2H4 and C2H5OH products, and (d) FEC2H4 / FEC2H5OH ratio.

[0021] Figure 6 1 is a product distribution diagram of the electrocatalytic reduction of CO2 by Cu / PTFE. In the figure, (a) to (e) are the product distribution diagrams of the electrocatalytic reduction of CO2 by Cu / PTFE, corresponding to the copper electrodes P-Cu of Examples 6 to 10, respectively. 100 ~ P-Cu 500 ; (f) is the maximum C of Cu sputtering thickness on electrocatalytic reduction of CO2 2+ The influence of product Faradaic efficiency.

[0022] Figure 7 The catalytic performance comparison of PTFE-based copper electrode Cu / PTFE at different current densities is shown in Figure 3. 2+ The Faraday efficiency of the product, (b) different thicknesses of C based on polytetrafluoroethylene 2+ Effect of fractional current density on the products; Effect of current density on (c) FEC2H4 / FEC2H5OH ratio, (d) Faradaic efficiency of H2 and CO products. DETAILED DESCRIPTION

[0023] The technical solution of the present invention is further described below through specific embodiments.

[0024] In the present invention, unless otherwise specified, the raw materials and equipment used can be purchased from the market or are commonly used in the art. The methods in the embodiments, unless otherwise specified, are all conventional methods in the art. Unless otherwise specified, parts are by weight, temperatures are expressed in ° C or at ambient temperature, and pressures are atmospheric pressure or near atmospheric pressure. There are many variations and combinations of reaction conditions (such as component concentrations, desired solvents, solvent mixtures, temperatures, pressures, and other reaction ranges) and conditions that can be used to optimize the purity and yield of the product obtained by the method, and only reasonable routine experiments will be required to optimize such method conditions.

[0025] Example 1. Preparation method of copper-based catalyst The method comprises the following steps: sputtering copper on a substrate to form a copper layer with a thickness of 100-500 nm (more preferably 100-300 nm) on the surface of the substrate to obtain a copper-based catalyst.

[0026] The copper is pure copper with a purity of 99.9% or more. The particle size of the copper is less than 100 nanometers, preferably 50-100 nm. The particle size of the copper has a significant effect on the performance of the copper-based catalyst; The substrate is carbon paper or polytetrafluoroethylene (PTFE). Carbon paper is a carbon fiber composite paper made of carbon fibers with high tensile strength, which are firmly connected together by carbon fibers. Carbon paper has good electrical conductivity and is very suitable for use as a catalyst backing layer, and metal nanoparticles can be synthesized on its surface. The present invention preferably uses SGL Carbon and SGL36BB, where SGL Carbon is the company name and BB represents the carbon paper model. This carbon paper has a PTFE layer and a microporous layer. This type of carbon paper is treated with PTFE hydrophobicity and coated with a layer of MPL (microporous layer); The sputtering power is 100-300 W, the sputtering rate is 10-20 nm / min, and the sputtering time is 300-2000 s.

[0027] 2. Preparation method of another copper-based catalyst The following steps are involved: Step 1: Sputter copper onto a substrate to form a copper layer with a thickness of 100-500 nm (more preferably 100-300 nm) on the surface of the substrate to obtain a copper-based catalyst.

[0028] The copper is pure copper with a purity of 99.9% or more. The particle size of the copper is less than 100 nanometers, preferably 50-100 nm. The particle size of the copper has a significant effect on the performance of the copper-based catalyst; The substrate is carbon paper or polytetrafluoroethylene (PTFE). Carbon paper is a carbon fiber composite paper made of carbon fibers with high tensile strength, which are firmly connected together by carbon fibers. Carbon paper has good electrical conductivity and is very suitable for use as a catalyst backing layer, and metal nanoparticles can be synthesized on its surface. The present invention preferably uses SGL Carbon and SGL36BB, where SGL Carbon is the company name and BB represents the carbon paper model. This carbon paper has a PTFE layer and a microporous layer. This type of carbon paper is treated with PTFE hydrophobicity and coated with a layer of MPL (microporous layer); The sputtering power is 100-300 W, the sputtering rate is 10-20 nm / min, and the sputtering time is 300-2000 s.

[0029] Step 2: further placing the copper-based catalyst obtained in step 1 into a metal salt solution for a replacement reaction to obtain a copper-containing bimetallic catalyst.

[0030] The bimetallic material is copper and palladium, and the mass proportion of copper in the bimetallic material is 20-50%. The metal salt solution is a palladium chloride solution, which is prepared by PdCl2 powder, deionized water and hydrochloric acid, and the palladium ion concentration in the prepared palladium chloride solution is 0.3-0.7 mmol / L; The replacement reaction can be carried out at room temperature and pressure without heating or pressurization, and the replacement reaction time is also very short, 3-20 minutes.

[0031] Example 1 A method for preparing a copper-based catalyst comprises the following steps: Carbon paper (SGL Carbon, SGL36BB) was used as the substrate, pure copper (purity 99.9%) was used as the target material, and the copper particle size was 80 nm. The sputtering power was set to 300 W, the sputtering rate was set to 16 nm / min, and the sputtering copper layer with a thickness of 100 nm was obtained by sputtering for 375 s. The carbon paper-based copper electrode Cu / CP was obtained and named C-Cu 100 .

[0032] Example 2 The difference from Example 1 is that the sputtering time is 750 s and the thickness of the sputtered copper layer is 200 nm. The details are as follows: A method for preparing a copper-based catalyst comprises the following steps: Carbon paper (SGL Carbon, SGL36BB) was used as the substrate, pure copper (purity 99.9%) was used as the target material, and the copper particle size was 80 nm. The sputtering power was set to 300 W, the sputtering rate was set to 16 nm / min, and the sputtering time was 750 s to obtain a sputtered copper layer with a thickness of 200 nm. The carbon paper-based copper electrode Cu / CP was obtained and named C-Cu200 .

[0033] Example 3 The difference from Example 1 is that the sputtering time is 1125 s and the thickness of the sputtered copper layer is 300 nm. The details are as follows: A method for preparing a copper-based catalyst comprises the following steps: Carbon paper (SGL Carbon, SGL36BB) was used as the substrate, pure copper (purity 99.9%) was used as the target material, and the copper particle size was 80 nm. The sputtering power was set to 300 W, the sputtering rate was set to 16 nm / min, and the sputtering was performed for 1125 s to obtain a sputtered copper layer with a thickness of 300 nm. The carbon paper-based copper electrode Cu / CP was obtained and named C-Cu 300 .

[0034] Example 4 The difference from Example 1 is that the sputtering time is 1500 s and the thickness of the sputtered copper layer is 400 nm. The details are as follows: A method for preparing a copper-based catalyst comprises the following steps: Carbon paper (SGL Carbon, SGL36BB) was used as the substrate, pure copper (purity 99.9%) was used as the target material, and the copper particle size was 80 nm. The sputtering power was set to 300 W, the sputtering rate was set to 16 nm / min, and the sputtering time was 1500 s to obtain a sputtered copper layer with a thickness of 400 nm. The carbon paper-based copper electrode Cu / CP was obtained and named C-Cu 400 .

[0035] Example 5 The difference from Example 1 is that the sputtering time is 1875 s and the thickness of the sputtered copper layer is 500 nm. The details are as follows: A method for preparing a copper-based catalyst comprises the following steps: Carbon paper (SGL Carbon, SGL36BB) was used as the substrate, pure copper (purity 99.9%) was used as the target material, and the copper particle size was 80 nm. The sputtering power was set to 300 W, the sputtering rate was set to 16 nm / min, and the sputtering was performed for 1875 s to obtain a sputtered copper layer with a thickness of 500 nm. The carbon paper-based copper electrode Cu / CP was obtained and named C-Cu 500 .

[0036] Example 6 A method for preparing a copper-based catalyst comprises the following steps: Polytetrafluoroethylene (PTFE) was used as the substrate, pure copper (purity 99.9%) was used as the target material, and the copper particle size was 80 nm. The sputtering power was set to 300 W, the sputtering rate was set to 16 nm / min, and the sputtering copper layer with a thickness of 100 nm was obtained by sputtering for 375 s. The PTFE-based copper electrode Cu / PTFE was obtained and named P-Cu 100 .

[0037] Example 7 The difference from Example 6 is that the thickness of the sputtered copper layer is 200 nm. The details are as follows: A method for preparing a copper-based catalyst comprises the following steps: Polytetrafluoroethylene (PTFE) was used as the substrate, pure copper (purity 99.9%) was used as the target material, and the copper particle size was 80 nm. The sputtering power was set to 300 W, the sputtering rate was set to 16 nm / min, and the sputtering time was 750 s to obtain a sputtered copper layer with a thickness of 200 nm, and a PTFE-based copper electrode Cu / PTFE was obtained, named P-Cu 200 .

[0038] Example 8 The difference from Example 6 is that the thickness of the sputtered copper layer is 300 nm. The details are as follows: A method for preparing a copper-based catalyst comprises the following steps: Polytetrafluoroethylene (PTFE) was used as the substrate, pure copper (purity 99.9%) was used as the target material, and the copper particle size was 80 nm. The sputtering power was set to 300 W, the sputtering rate was set to 16 nm / min, and the sputtering was performed for 1125 s to obtain a sputtered copper layer with a thickness of 300 nm. The PTFE-based copper electrode Cu / PTFE was obtained and named P-Cu 300 .

[0039] Example 9 The difference from Example 6 is that the thickness of the sputtered copper layer is 400 nm. The details are as follows: A method for preparing a copper-based catalyst comprises the following steps: Polytetrafluoroethylene (PTFE) was used as the substrate, pure copper (purity 99.9%) was used as the target material, and the copper particle size was 80 nm. The sputtering power was set to 300 W, the sputtering rate was set to 16 nm / min, and the sputtering time was 1500 s to obtain a sputtered copper layer with a thickness of 400 nm, and a PTFE-based copper electrode Cu / PTFE was obtained, named P-Cu 400 .

[0040] Example 10 The difference from Example 6 is that the thickness of the sputtered copper layer is 500 nm. The details are as follows: A method for preparing a copper-based catalyst comprises the following steps: Polytetrafluoroethylene (PTFE) was used as the substrate, pure copper (purity 99.9%) was used as the target material, and the copper particle size was 80 nm. The sputtering power was set to 300 W, the sputtering rate was set to 16 nm / min, and the sputtering was performed for 1875 s to obtain a sputtered copper layer with a thickness of 500 nm. The PTFE-based copper electrode Cu / PTFE was obtained and named P-Cu 500 .

[0041] Embodiment 11 The difference from Example 9 is that Cu / PTFE is further made into a Cu-Pd / PTFE bimetallic catalyst. The details are as follows: A method for preparing a copper-based catalyst comprises the following steps: Step 1: Use polytetrafluoroethylene (PTFE) as the substrate and pure copper (purity 99.9%) as the target material. The copper particle size is 80 nm. The sputtering power is set to 300 W, the sputtering rate is set to 16 nm / min, and the sputtering time is 1500 s to obtain a sputtered copper layer with a thickness of 400 nm. The Cu / PTFE catalyst is named P-Cu. 400 .

[0042] Step 2: Weigh 8.87×10 -4 g of PdCl2 powder, use 100 mL of deionized water and 1 g of hydrochloric acid solution to prepare a 0.5 mM PdCl2 solution, put the Cu / PTFE catalyst substrate prepared in step 1 into the PdCl2 solution and let it stand for 5 min for replacement reaction to obtain a Cu-Pd / PTFE bimetallic catalyst.

[0043] Performance Characterization 1. XRD Characterization Figure 1 The XRD characterization diagram of copper electrodes with different copper sputtering thicknesses. Figure a is a carbon paper-based copper electrode Cu / CP, C-Cu 100 ~ C-Cu 500 Corresponding to the copper electrodes of Examples 1 to 5 respectively; b is a PTFE-based copper electrode PTFE / CP, P-Cu 100 ~ P-Cu 500 They correspond to the copper electrodes of Example 6 to Example 10 respectively.

[0044] from Figure 1Look: Compared with the standard card data (Cu#PDF04-0836, C#PDF26-1027), it can be seen that the main crystal planes of metallic copper in the sputtered copper electrode are Cu(111), Cu(200) and Cu(220). As the sputtering thickness increases, the intensity of the 43.32° diffraction peak corresponding to the Cu(111) crystal plane gradually increases. However, the increase in the diffraction peak intensity of the Cu(200) crystal plane at 50.45° and the Cu(220) crystal plane at 74.12° is not obvious. This shows that as the thickness of magnetron sputtering deposited copper increases, the Cu(111) crystal plane begins to have a preferential orientation.

[0045] 2. SEM Characterization Figure 2 The SEM electron micrographs of copper electrodes with different copper sputtering thicknesses (scale bar: 500 nm). In the figure, (a) is a SEM electron micrograph of a blank carbon paper, and (b)-(f) correspond to SEM electron micrographs of metal copper loaded on carbon paper with a thickness of 100-500 nm in Examples 1-5, respectively.

[0046] Application Examples The copper-based catalysts prepared in the above examples were used to electrocatalyze CO2 to produce multi-carbon products at a voltage of 3.5-4.5 V, preferably 3.8-4.3 V, to test their catalytic performance. The results are as follows: 1. Comparison of catalytic performance of Cu electrode and Cu-Pd bimetallic electrode The CO2 electrocatalytic test was carried out on the metal Cu electrode catalyst of Example 4 and the Cu-Pd bimetallic electrode catalyst of Example 11, and the results are as follows: Figure 3 As shown in the figure, (a) is the Cu electrode and (b) is the Cu-Pd bimetallic electrode.

[0047] from Figure 3 Look, when the current density is 150 mA / cm 2 When Cu is C 2+ The Faraday efficiency FE is 78.76%, and the Faraday efficiency of ethylene is 45.23%. After the Pd element is introduced into Cu, C 2+ The Faraday efficiency was increased to 80.42%, and the Faraday efficiency of ethylene was increased to 51.36%. It can be seen that the Cu-Pd bimetallic catalyst can achieve higher selectivity for multi-carbon products.

[0048] 2. Comparison of catalytic performance of carbon paper-based copper electrodes Cu / CP with different thicknesses Figure 4 1 is a product distribution diagram of the electrocatalytic reduction of CO2 using Cu / CP. (a)-(e) in the figure are the product distributions of the electrocatalytic reduction of CO2 using Cu / CP, corresponding to the copper electrodes C-Cu of Examples 1 to 5, respectively.100 ~ C-Cu 500 ; (f) indicates the effect of Cu sputtering thickness on the maximum C of electrocatalytic reduction of CO2 2+ The influence of product Faradaic efficiency.

[0049] from Figure 4 Look: Cu / CP (C-Cu 100 ), FEH2 initially decreased from 22.9% to 15.3%, and then increased to 29.12% as the current density increased from 100 mA / cm2 to 300 mA / cm2. At the same time, FECO decreased from 19.16% to 5.35%, while FECH4 increased from 5.26% to 29.51%. 2 When FEC2H4, FECH3COOH and FEC2H5OH were 31.15%, 7.3% and 24.48% respectively, and FEC 2+ When the thickness of sputtered copper was increased to 200 nm, HER was significantly suppressed. 2 In addition, FECO decreased from 30.76% to 9.45%, while FEC 2+ The product was obtained from a current density of 100 mA / cm 2 When the current density is increased to 300 mA / cm 2 64.87% at a current density of 250 mA / cm 2 Maximum FEC is achieved when 2+ About 70.45%. C-Cu 300 、C-Cu 400 and C-Cu 500 The distribution and trend of the electrocatalytic CO2 reduction products are similar to those of C-Cu200.

[0050] Figure 4 (f) Comparison of the maximum FEC of Cu / CP electrodes with different sputtering layer thicknesses. 2+ At a current density of 200 mA / cm 2 When C-Cu 100 Maximum FEC of the electrode 2+ As the sputtering layer thickness continues to increase, especially at 200 nm and 300 nm, the FEC 2+ The product selectivity was always above 60%. Specifically, at 250 mA / cm 2 and 300 mA / cm 2 When C-Cu 200 and C-Cu300 FEC 2+ The maximum values ​​are 70.45% and 70.44% respectively. After further increasing the sputtering thickness, the maximum FEC 2+ There was no significant increase in C-Cu 400 and C-Cu 500 The maximum values ​​are 69.72% and 70.78% respectively.

[0051] Figure 5 The catalytic performance comparison of carbon paper-based copper electrode Cu / CP at different current densities is shown in Figure 3. 2+ Faraday efficiency of the product, (b) different thicknesses of carbon paper as substrate C 2+ Effect of fractional current density on the products; Effect of current density on (c) Faradaic efficiency of C2H4 and C2H5OH products, and (d) FEC2H4 / FEC2H5OH ratio.

[0052] from Figure 5 Look: As the current density increases from 100 mA / cm 2 Increase to 300 mA / cm 2 When using copper electrodes with a thickness of more than 200 nm, C 2+ The product increases rapidly at first and then reaches saturation. Figure 5 As can be seen in a, the performance of the Cu / CP thin electrode drops sharply. 2+ The partial current density of the product increases almost linearly with the current density. 2 When C-Cu 500 Electrode C 2+ The maximum partial current density of the product is 212.34 mA / cm 2 , is C-Cu 100 The thickness of the sputtered layer is 1.68 times that of the electrode. This indicates that increasing the thickness of the sputtered layer can provide more abundant reaction sites. 500 The electrodes are the same, C-Cu 300 and C-Cu 400 The partial current density of the electrode also exceeded 200 mA / cm 2 , which means that as the thickness of the sputtered layer increases, the number of reactive sites also increases slightly ( Figure 5 b). C of sputtered copper electrode on carbon paper substrate 2+ The products are mainly C2H4 and C2H5OH. 100 and C-Cu 300The selectivities of the electrodes were 17.4-31.15% and 29.15-39.26% for C2H4, and 13.47-24.45% and 13.86-24.34% for C2H5OH. Figure 5 c). C-Cu 300 The FEC2H4 is much higher than C-Cu 100 , even at 300mA / cm 2 In addition, Figure 5 d shows that the C2H4 / C2H5OH ratio increases with the increase of sputtered layer thickness, while it decreases with the increase of current density.

[0053] 3. Comparison of catalytic performance of PTFE-based copper electrodes Cu / PTFE with different thicknesses Figure 6 1 is a product distribution diagram of the electrocatalytic reduction of CO2 by Cu / PTFE. In the figure, (a) to (e) are the product distributions of the electrocatalytic reduction of CO2 by Cu / PTFE, corresponding to the copper electrodes P-Cu of Examples 6 to 10, respectively. 100 ~ P-Cu 500 ; (f) is the maximum C of Cu sputtering thickness on electrocatalytic reduction of CO2 2+ The influence of product Faradaic efficiency.

[0054] from Figure 6 See: (a)-(e) depict the FEH2, FECO and FEC when using Cu / PTFE electrodes with different sputtered layer thicknesses. 2+ The distribution of is a function of current density. When the current density increases from 100 mA / cm 2 Increase to 300 mA / cm 2 When FECO decreases gradually, FEC 2+ This is consistent with the case of Cu / CP. As the current density increases, the reaction kinetics of the CC coupling process accelerates, which is beneficial to C 2+ The formation of products. 200 For electrodes, FECO is from 100 mA / cm 2 12.62% when it drops to 300mA / cm 2 4.26% when FEC 2+ It increased from 65.42% to 66.1%. Figure 6 P-Cu in e 100 、P-Cu 200 、P-Cu 300 、P-Cu 400 and P-Cu 500 The Cu / PTFE electrode was charged at a current density of 200 mA / cm2 The highest C 2+ The selectivity, regardless of the copper layer thickness, was 66.14%, 67.25%, 71.53%, 71.76%, and 61.98%, respectively. It is worth noting that the thicker sputtered layer may reduce the pore size, thereby hindering the diffusion of CO2 and H2O, resulting in a decrease in the CO2RR electrocatalytic activity. In addition, it was observed that higher current density promoted the generation of CH4, especially in the P-Cu 100 and P-Cu 500 In the electrode. As the current density increases, the P-Cu 100 The FECH4 of the electrodes increased from 1.05% to 9.49%, while the P-Cu 500 The FECH4 of the electrode increased from 0.11% to 5.08%, which means that the protonation process of *H promoted the generation of CH4. Compared with the Cu / CP electrode, the Cu / PTFE electrode always showed lower FEH2 and FECO (less than 10%) and higher FEC in a wider current density range. 2+ , where C 2+ The products are also mainly C2H4 and C2H5OH.

[0055] Figure 7 The catalytic performance comparison of PTFE-based copper electrode Cu / PTFE at different current densities is shown in Figure 3. 2+ The Faraday efficiency of the product, (b) different thicknesses of C based on polytetrafluoroethylene 2+ Effect of fractional current density on the products; Effect of current density on (c) FEC2H4 / FEC2H5OH ratio, (d) Faradaic efficiency of H2 and CO products.

[0056] from Figure 7 Look: As the current density increases from 100 mA / cm 2 Increase to 300 mA / cm 2 , Cu / PTFE FEC 2+ First it rises and then it falls. For example, the FEC of the P-Cu500 electrode 2+ It increased from 58.21% to 61.98% and then decreased to 46.37%, while P-Cu 200 FEC of electrodes 2+ It remains relatively stable ( Figure 7 a). As for C 2+ The partial current density of the product shows a similar trend with increasing current density, regardless of the thickness of the copper layer ( Figure 7 b). According to Figure 7 c, C 2+ The product is mainly C2H4. Interestingly, P-Cu300 The electrode is at 100 mA / cm 2 The FEC2H4 / FEC2H5OH ratio is the largest at 2.41, while P-Cu 500 The electrode is at 100 mA / cm 2 The FEC2H4 / FEC2H5OH ratio is the lowest at 0.91 ( Figure 7 c). Comparison of P-Cu 100 and P-Cu 400 It can be found that the FEH2 and FECO of the electrode increase with the current density exceeding 200 mA / cm 2 , P-Cu 100 and P-Cu 400 The FEH2 of the electrode increased significantly, while the FECO decreased gradually.

[0057] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technician familiar with this profession can make some changes or modifications to equivalent embodiments of equivalent changes using the technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the technical solution of the present invention.

Claims

1. A method for preparing a copper-based catalyst, characterized in that: Sputtering copper onto a substrate to form a copper layer with a thickness of 100-500 nm on the surface of the substrate to obtain a copper-based catalyst; the particle size of the copper is less than 100 nm; the sputtering power is 100-300 W and the rate is 10-20 nm / min; Alternatively, the copper-based catalyst is further placed in a metal salt solution for a replacement reaction to obtain a copper-containing bimetallic catalyst; the mass proportion of copper in the bimetallic catalyst is 20-50%.

2. The method for preparing a copper-based catalyst according to claim 1, characterized in that: The substrate is carbon paper or PTFE.

3. The method for preparing a copper-based catalyst according to claim 1 or 2, characterized in that: The splash time is 300-2000 s.

4. The method for preparing a copper-based catalyst according to claim 1, characterized in that: The particle size of copper is 50-100 nm.

5. The method for preparing a copper-based catalyst according to claim 1 or 4, characterized in that: The thickness of the copper layer is 100-300 nm.

6. The method for preparing a copper-based catalyst according to claim 1, characterized in that: The bimetallic materials are copper and palladium, and the palladium ion concentration in the metal salt solution is 0.3-0.7 mmol / L.

7. The method for preparing a copper-based catalyst according to claim 6, characterized in that: The metal salt solution is a palladium chloride solution, which is prepared from PdCl2 powder, deionized water and hydrochloric acid.

8. The method for preparing a copper-based catalyst according to claim 1, 6 or 7, characterized in that: The replacement reaction is carried out at room temperature and the reaction time is 3-20 min.

9. Use of the copper-based catalyst prepared by any one of claims 1 to 8 in electrocatalytic CO2 production of multi-carbon products, characterized in that: Current density is 200-300 mA*cm -2 , FEC 2+ >65%.

10. The method for preparing the copper-based catalyst according to claim 9 and its application in electrocatalyzing CO2 to prepare multi-carbon products, characterized in that: The current density is 200 mA*cm -2 , the thickness of the copper layer is 100-300 nm, FEC 2+ >70%.

Citation Information

Patent Citations

  • Modification of copper foil electrode and CO2 electrocatalytic reduction reaction of modified copper foil electrode

    CN108677179A